Quality of pharmaceutical and related products in Peru inspected by DIGEMID, 2002–2006 - Coral Monge, María Margarita (2009)
2843 inquiries were checked, pharmaceuticals and related products, made by the Control and Monitoring Equipment Establishments of DIGEMID from 2002 to 2006. The physicochemical and microbiological analyses were realized by the National Institute of Health and then evaluated by the Control and Monitoring Product. Of the whole of products were found that 65% are satisfied and 35% did not comply. The results of the non-compliant were classified to determine the main observations about quality: Unauthorized labeling 40%, Deficient product 27%, Critical 17%, Specification change 14%, Without sanitary record 1% and Unauthorized presentation form 1 %. In their investigation: 45% were brand name drugs, generic drugs 30%, 10% medical supplies and 9% cosmetics. Were in conformity: brand drugs 69%, generic drugs 64%, medical supplies 60% and cosmetics 68%. Regarding the type of pharmaceutical establishment in accordance presenting their products are: labs 69%, drugstores 62%, importing 67%. By country of origin, the line were 71% home and 59% foreign.